2021
DOI: 10.1155/2021/9207541
|View full text |Cite
|
Sign up to set email alerts
|

Active Management of Third Stage of Labor: Practice and Associated Factors among Obstetric Care Providers in North Wollo, Amhara Region, Ethiopia

Abstract: Background. World Health Organization strongly recommends that every obstetrical provider at birth needs to have knowledge and skills on active management of the third stage of labor and use it routinely for all women. However, implementation of this lifesaver intervention by skilled birth attendants is questionable because 3% to 16.5% of women still experience postpartum hemorrhage. Even though coverage of giving births at health facilities in Ethiopia increases, postpartum hemorrhage accounts for 12.2% of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…This implies that 60% of laboring mothers might face life-threatening complications like severe hemorrhage and its related complications. This finding is consistent with previous studies in Ethiopia (Tigray 43.3%) and Nigeria (41.7%), but higher than studies in Sudan (26.7%), and Ethiopia such as in Kembata Tembaro zone (29.8%), Amhara region (32.3%), Sidama zone (32.8%) and Hawassa city (15.7%) [ 26 28 , 38 , 40 – 42 ]. The disparity could be attributed to the study period, educational level, and training.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This implies that 60% of laboring mothers might face life-threatening complications like severe hemorrhage and its related complications. This finding is consistent with previous studies in Ethiopia (Tigray 43.3%) and Nigeria (41.7%), but higher than studies in Sudan (26.7%), and Ethiopia such as in Kembata Tembaro zone (29.8%), Amhara region (32.3%), Sidama zone (32.8%) and Hawassa city (15.7%) [ 26 28 , 38 , 40 – 42 ]. The disparity could be attributed to the study period, educational level, and training.…”
Section: Discussionsupporting
confidence: 91%
“…Presence of birth assistants in addition to MCPs increased the likelihood of good practice of AMTSL. This is in harmony with studies in Ethiopia and Nigeria [ 28 , 38 ]. The presence of assistants is one of the critical factors in performing good AMTSL and this is true in all maternity procedures where only team efforts will provide adequate care.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2 (Suppl) , May 2022 reported that 10% of all maternal deaths were prevented with timely, effective and full use of clinical guidelines for active management of third stage of labor. This reduces the incidence of postpartum hemorrhage, the need for blood transfusion, and the use of therapeutic utero tonics during the third stage of labor, improving women's health and reducing maternal mortality that is central to the 2030 agenda for sustainable development strategy (9,10) .…”
Section: Introductionmentioning
confidence: 99%